2009
DOI: 10.1007/s12664-009-0050-z
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported treatment adherence in inflammatory bowel disease in Indian patients

Abstract: Over 80% of patients with IBD in this survey were non-adherent to medical treatment; forgetfulness was mentioned as the most common cause. Non-adherent patients were more likely to relapse. Patients need to be educated regarding the need for adherence to treatment in IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 19 publications
(15 reference statements)
2
18
2
Order By: Relevance
“…However, patient-estimated adherence rates over the past 7 days were lower. Similar to rates observed in previous observational data [6,7,11,12,14,16-20], these low adherence rates are troublesome, given that poor adherence with 5-ASA therapy is linked to an increased risk of flare and higher medical costs [11-13,21]. In turn, increased disease activity can also result in deterioration of patient quality of life [2,22-24].…”
Section: Discussionsupporting
confidence: 68%
“…However, patient-estimated adherence rates over the past 7 days were lower. Similar to rates observed in previous observational data [6,7,11,12,14,16-20], these low adherence rates are troublesome, given that poor adherence with 5-ASA therapy is linked to an increased risk of flare and higher medical costs [11-13,21]. In turn, increased disease activity can also result in deterioration of patient quality of life [2,22-24].…”
Section: Discussionsupporting
confidence: 68%
“…In addition to the use of complementary therapy there is a tendency towards significantly low levels of adherence to 5-aminosalicylic acid treatment among patients of South Asian origin. This has been reported in studies both from India61 and the UK 62…”
Section: Inflammatory Bowel Diseasesupporting
confidence: 65%
“…Disease duration, location and activity as well as a recent diagnosis and infrequent visits to physician were related to noncompliance (4,9). In addition, drug-related factors such as type of drugs, burden of drug regimens, multiple therapies, and complicated dosage regimens increased the risk of forgetfulness (2,4,10). The first studies investigating IBD patient's information needs in the 70's to 90's showed concerns focused on aetiology, symptoms, diet, and on 6 therapies and their related risks and benefits (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%